NARRATIVES OF CHANGE: TEACHERS’ LIVED EXPERIENCES OF ONLINE PROFESSIONAL COMMUNITIES AND THEIR IMPACT ON TEACHING PRACTICE - OLOBA, Peter Babajide; DZINOREVA , Tendayi (International Journal of Social and Educational Innovation (IJSEIro), 2026)
Continuous Professional Development (CPD) is widely recognised as essential for improving teaching quality; however, traditional models are often criticised for being prescriptive, decontextualised, and limited in their impact on classroom practice and teacher beliefs. The emergence of online professional communities offers alternative, teacher-driven spaces for professional learning, yet there remains limited understanding of how teachers’ lived experiences within these environments influence their teaching practices and professional beliefs. This study aimed to explore teachers’ lived experiences of participation in online CPD communities and examine how such engagement shapes their pedagogical practices and professional beliefs. A qualitative approach, grounded in a constructivist paradigm, was adopted. Data were collected from 100 teachers through an open-ended questionnaire, followed by semi-structured interviews with 20 purposively selected participants. The data were analysed using thematic analysis. The findings revealed that participation in online CPD communities significantly influenced teaching practice through improved learner engagement, resource mobilisation and curriculum development, pedagogical advancement, and innovation. Additionally, teachers experienced shifts in professional beliefs related to assessment, collaboration, leadership, and identity while demonstrating increased agency and confidence in their practice. These findings show that online communities function as dynamic spaces for collaborative learning, reflective practice, and professional transformation. The study recommends the design of context-responsive and inclusive CPD platforms, the promotion of teacher voice and leadership, and the strengthening of collaborative and interactive learning environments. It concludes that online CPD has the potential to transform professional development into a more participatory, flexible, and impactful process that supports both practice and belief transformation.